Terror in the name of God : why religious militants kill - Stern, Jessica, 1958- (New York : Ecco, 2003)
"For four years, Jessica Stern interviewed extremist members of three religions around the world: Christians, Jews, and Muslims. Traveling extensively - to refugee camps in Lebanon, to religious schools in Pakistan, to prisons in Amman, Asqelon, and Pensacola - she discovered that the Islamic jihadi in the mountains of Pakistan and the Christian fundamentalist bomber in Oklahoma have much in common." Stern's extensive interaction with the faces behind the terror provide unprecedented insight into acts of inexplicable horror, and enable her to suggest how terrorism can most effectively be countered."--BACK COVER.
Pt. I. Grievances That Give Rise to Holy War -- 1. Alienation -- 2. Humiliation -- 3. Demographics -- 4. History -- 5. Territory -- Pt. II. Holy War Organizations -- 6. Inspirational Leaders and Their Followers -- 7. Lone-Wolf Avengers -- 8. Commanders and Their Cadres -- 9. The Ultimate Organization: Networks, Franchises, and Freelancers -- 10. Conclusion/Policy Recommendations.
Includes bibliographical references (p. 297-359) and index.
Keywords: Terrorism -- Religious aspects -- Christianity; Violence -- Religious aspects -- Christianity; Terrorism -- Religious aspects -- Judaism; Violence -- Religious aspects -- Judaism; Terrorism -- Religious aspects -- Islam; Violence -- Religious aspects -- Islam; Religious fanaticism; Religious militants